2001
DOI: 10.1095/biolreprod64.3.764
|View full text |Cite
|
Sign up to set email alerts
|

Na+ Reabsorption in Cultured Rat Epididymal Epithelium via the Na+/Nucleoside Cotransporter1

Abstract: The effect of nucleoside on Na+ reabsorption via Na+/nucleoside cotransporter in cultured rat epididymal epithelia was studied by short-circuit current (Isc) technique. Guanosine added apically stimulated Isc in a dose-dependent manner, with a median effective concentration (EC50) of 7 +/- 2 microM (mean +/- SEM). Removal of Na+ from the apical bathing solution or pretreatment with a nonspecific Na+/nucleoside cotransporter inhibitor, phloridzin, completely blocked the Isc response to guanosine. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The relative importance of ADA1 and CNTs on nasal and bronchial epithelia was determined by comparing the effects of optimal concentrations of EHNA () (10 μM; Figure B) and phloridzin ( ) (2 mM; Figure B) on the elimination of ASL adenosine over a concentration range including basal ( 5 , 72 , 73 ) and pathological (>100 μM) ( , ) conditions. We showed that ADA1 and CNT activities account for 40% and 60% of the elimination of a physiological (1 μM) adenosine concentration on nasal epithelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative importance of ADA1 and CNTs on nasal and bronchial epithelia was determined by comparing the effects of optimal concentrations of EHNA () (10 μM; Figure B) and phloridzin ( ) (2 mM; Figure B) on the elimination of ASL adenosine over a concentration range including basal ( 5 , 72 , 73 ) and pathological (>100 μM) ( , ) conditions. We showed that ADA1 and CNT activities account for 40% and 60% of the elimination of a physiological (1 μM) adenosine concentration on nasal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of paracellular diffusion was tested in Ussing chambers by comparing the permeability coefficients of adenosine and mannitol. The functional expression of CNTs and ENTs was investigated by use of the broad-range inhibitors phloridzin ( ) and dipyridamole ( , ), respectively. The CNT isoforms were identified by competition assays, kinetic properties, and mRNA expression.…”
mentioning
confidence: 99%
“…This Na + /nucleoside cotransporter has been cloned recently and only a few studies have been reported. However, a role for CNT2 has been suggested in sodium reabsorption over epididymal epithelium [15]. The upregulation of CNT2 is probably of importance for the uptake of nucleosides and sodium during cholera and related diarrhoeal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbed sugars are then transported over the basolateral membrane by facilitative sugar transporters (GLUTs), whereas the reabsorbed Na + can be transported to the serosal side by an active Na + /K + ATPase [14]. In a similar manner, Na + is reabsorbed together with nucleosides via the concentrative nucleoside transporter 2 (CNT2) [15].…”
Section: Introductionmentioning
confidence: 99%